Não chuta que é macumba: a patrimonialização do Ilê Axé Opô Afonjá e a sua contribuição no fortalecimento de uma identidade afro-religiosa no Brasil - Santos, Cláudio de Jesus (2019)
Candomblé's terreiros reach the twenty-first century by demarcating their space in the composition of the Brazilian cultural heritage by preserving the memory of its people and its community, bringing to itself an importance that goes beyond the cult of the orixás. It is for this reason that we increasingly perceive the connections between spaces chosen as patrimony and that harbor religious functions, that we intend to reflect on the implications generated in the religious field, more specifically in the constructions of the meaning of religion. With this we are interested in knowing if the process of patrimonialization of the terreiros (rural property) makes possible the strengthening of an afro-religious identity redefined for Candomblé in Brazil. It is also of specific interest to analyze the construction of symbolic cultural goods and strategies for the legitimation of a "sacred patrimony" by Afro-religious communities. With the purpose of reaching the proposed objective, we made use of a bibliographical revision allied to the ethnographic method, with Ilê Axé Opô Afonjá, located in the State of Bahia, establishing an interdisciplinary methodological action between the Sciences of Religion and other fields of knowledge. The partial results point to the change of a "religious status" in contemporary candomblé from the process of patrimonialization thus generating new forms of organization in the universe of religions of African matrix and contributing to its mediatic dissemination.